Percepatan Proses Konsolidasi Tanah Lempung Dengan Aplikasi Tekanan Vakum dan Drainase Vertikal - arhab; Nurly Gofar (Rekayasa Sipil, 2023)
This paper presents the performance of PVD and vacuum consolidation as ground improvement method at the construction of Kayu Agung – Palembang Toll Road. The analysis was based on observation data collected between STA 00+000 and STA 09+000. The PVD was installed to a depth where the conus resistance of 80 kPa was achieved. Thus, the length of PVD varies from 5 to 13 m while the actual depth of clay deposit could reach 20 m. As many as 42 settlement plate data were collected and analyzed using Asaoka method to obtain the predicted final settlement, the coefficient of consolidation and the time to reach 90% degree of consolidation. The results were compared with the duration of vacuum consolidation application and the recorded settlement when the vacuum pressure was stopped i.e., when settlement plate recorded no differential settlement in three readings. The duration of vacuum consolidation application generally longer than the t90 predicted by the method and the actual settlement was larger than the predicted final settlement.  This study concluded that the variation of the t90 and the magnitude of settlement at t90 have close relationship with the length of PVD and the condition of the soil layer.